Adrenal Ganglioneuroma with Multifocal Retroperitoneal Extension: A Challenging Diagnosis. (16th August 2011) - Oderda, Marco; Cattaneo, Elena; Soria, Francesco; Barreca, Antonella; Chiusa, Luigi; Morelli, Bruno; Zitella, Andrea; Gontero, Paolo
Abstract : A ganglioneuroma (GN) is the rarest and most benign of the neuroblastic tumors and originates from neural crest cells wherever sympathetic nervous tissue exists, such as in the retroperitoneum and adrenal gland. The diagnosis can be very challenging, given the rarity and asymptomatic presentation of this neoplasia, and can be achieved only by means of histological evaluation. Although benign, a few cases of metastatic GNs have been reported in the literature. The prognosis, however, seems to be excellent after surgical resection. We describe a rare case of multifocal retroperitoneal GN, diagnosed incidentally in a 46-year-old woman, with para-aortic and adrenal localizations. After intraoperative pathological diagnosis was made, complete excision of all the visible masses was performed. The postoperative period was uneventful and she was recurrence free 3 months after surgery. To our knowledge, this is the first case report of a multifocal retroperitoneal GN. Among the broad differential diagnoses of adrenal incidentalomas, an adrenal location of neuroblastic tumors should not be forgotten.